2014
DOI: 10.2139/ssrn.2449213
|View full text |Cite
|
Sign up to set email alerts
|

Do Corporate Tax Cuts Reduce International Profit Shifting?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
2
0
0
Order By: Relevance
“…These accounts include: fixed asset accounts related to depreciation expense, tax expense paid, differences in recognition of sales or income, and recognition of other income. The results of this study are in line with previous research in other countries such as: in China [2], in Korea [5], in France [6], and in Germany [7].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These accounts include: fixed asset accounts related to depreciation expense, tax expense paid, differences in recognition of sales or income, and recognition of other income. The results of this study are in line with previous research in other countries such as: in China [2], in Korea [5], in France [6], and in Germany [7].…”
Section: Resultssupporting
confidence: 92%
“…Warsini [4] found evidence that public companies in Indonesia implemented a tax avoidance strategy through income decreasing in financial reporting for 2 years prior to the enactment of the tax rate reduction in the 2010. Similar research results were also found in other countries when there was a reduction in tax rates such as in China [2], in Korea [5], in France [6], and in Germany [7]. These studies have found that companies undertake an income shifting strategy by arranging financial statements for one period before the enactment of lower tax rates by accelerating expense recognition and delaying revenue recognition.…”
Section: Introductionsupporting
confidence: 78%